Nitrogen levels associated with the application of growth regulator in cotton (Research, Society and Development, 2021)
The adjustment in the amounts of nitrogen, to meet the nutritional needs of the crop, and the growth regulator, to adapt and homogenize the size of the cotton is an important technical aspect, in order to enable the expression of all the productive potential of modern cotton cultivars. Thus, the objective of this work was to verify the effects of the modes of application of growth regulator and nitrogen doses in coverage on the vegetative and reproductive development of cotton. The experiment was carried out in the experimental area of ​​the State University of Mato Grosso do Sul - University Unit of Aquidauana (UEMS / UUA), in soil classified as dystrophic Red Argisol. The experimental design used was in randomized blocks, in a 3x4 split plot scheme, with four replications. The treatments consisted of the combination of three modes of growth regulator applications (control without application, single dose and split dose), using the recommended dose of the commercial product (0.2 L ha-1), and four doses of nitrogen in coverage (0, 80, 160 and 240 kg ha-1). Plant height, height of insertion of the first boll, diameter of the stem, average mass of boll, fiber yield and cotton seed yield were evaluated. The growth regulator reduces plant height by up to 25% and stem diameter by approximately 12% and increases the mass of bolls by up to 10.2%, but does not increase fiber yield and seed cotton productivity.